2019
DOI: 10.1016/j.cmet.2018.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Combined Inhibition of DYRK1A, SMAD, and Trithorax Pathways Synergizes to Induce Robust Replication in Adult Human Beta Cells

Abstract: Highlights d Adult human pancreatic beta cells can be induced to proliferate at high rates d Driven by synergy between DYRK1A inhibitors and TGFb superfamily inhibitors d Reflects activation of cyclins and CDKs accompanied by CDK inhibitor suppression d Proliferation occurs in type 2 diabetic beta cells, with enhanced differentiation SUMMARYSmall-molecule inhibitors of dual-specificity tyrosine-regulated kinase 1A (DYRK1A) induce human beta cells to proliferate, generating a labeling index of 1.5%-3%. Here, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
218
1
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 126 publications
(238 citation statements)
references
References 69 publications
(161 reference statements)
13
218
1
6
Order By: Relevance
“…In this setting, TAC and SIR affect human β cell function without altering β cell proliferation or death. This adds to a growing body of literature highlighting differences in how human islets respond in vivo versus in vitro, including in their ability to proliferate, differentiate, and respond to metabolic stressors such as hyperglycemia or dyslipidemia (21,(40)(41)(42)(43)(44). Thus, these results highlight that in vitro may not always reflect in vivo mechanisms and emphasize the value of studying human islets in a transplantation model.…”
Section: Discussionmentioning
confidence: 79%
“…In this setting, TAC and SIR affect human β cell function without altering β cell proliferation or death. This adds to a growing body of literature highlighting differences in how human islets respond in vivo versus in vitro, including in their ability to proliferate, differentiate, and respond to metabolic stressors such as hyperglycemia or dyslipidemia (21,(40)(41)(42)(43)(44). Thus, these results highlight that in vitro may not always reflect in vivo mechanisms and emphasize the value of studying human islets in a transplantation model.…”
Section: Discussionmentioning
confidence: 79%
“…This study does not address the extent to which BrdU, marking S-phase entry, predicts completion of the cell cycle and production of two daughter cells. Evidence supporting the conclusion that some BrdU-labeled b-cells do successfully complete cell division include the many studies showing that BrdU labeling correlates with other proliferation markers such as Ki67, PCNA (proliferating cell nuclear antigen), and pHH3 (17,34,35), the documented increase in b-cell number under conditions when BrdU labeling is increased in vitro (17,36,37) and in vivo (33), and our current data showing BrdU(+) nuclei in mitosis ( Fig. 4G) and colabeling with pHH3 (Supplementary Fig.…”
Section: Discussionmentioning
confidence: 97%
“…One study used human islets to show that beta cells can be induced to proliferate at a faster rate both in vitro and in vivo by synergistic inhibition of the DYRK1A and TGFβ superfamily signaling pathways. The authors demonstrated that the inhibition of these pathways by pharmacological agents may not only increase the number of beta cells but also their differentiation markers, in islets from both nondiabetic and T2D donors [102]. The detailed mechanistic studies using human islets highlighted an increase in the proliferation rate of beta cells following the disruption of SMAD-mediated activation of the cell cycle inhibitors CDKN1A and CDKN1C.…”
Section: Regeneration Of Human Beta Cellsmentioning
confidence: 99%